Performance investigation of transcritical carbon dioxide refrigeration cycle - Baheta, A.T. (Elsevier B.V., 2015)
CO2 has low critical pressure and temperature. This gives an opportunity CO2 cycles to work in a transcritical nature where heat rejection and absorption are done at supercritical and subcritical conditions, respectively. However, this characteristic posed some performance issues for CO2 refrigeration cycle such as the pressure and temperature of CO2 becomes independent of one another above the critical point thus specifying the operating conditions would be tough. It is also important to identify the optimum cooler pressure and control it; in order to get high cycle coefficient of performance (COP). Thus, the objective of this paper is to investigate the performance of a transcritical CO2 compression refrigeration cycle for different parameters and evaluate its COP. To achieve that, a refrigeration cycle was modeled using thermodynamic concepts. Then, the model was simulated for various parameters that were manipulated to investigate the cycle performance. Maintaining other operating parameters constant the highest COP was 3.24 at 10MPa gas cooler pressure. It was also observed that the cycle is suitable for air-condition application than refrigeration cycle, as COP increases when the evaporator temperature increases. Simulations were conducted using EXCEL developed program. The results can be used in the design of CO2 refrigeration cycle. Â© 2015 Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license.